Maternal chronic stress correlates with serum levels of cortisol, glucose and C-peptide in the fetus, and maternal non chronic stress with fetal growth. (April 2020) - Valsamakis, Georgios; Papatheodorou, Dimitrios; Chalarakis, Nikolaos; Manolikaki, Maria; Margeli, Alexandra; Papassotiriou, Ioannis; Barber, Thomas M.; Kumar, Sudhesh; Kalantaridou, Sophia; Mastorakos, George
Highlights: Pregnancy stressors associate with changes in maternal and fetal HPA axes. Maternal non chronic stress impacts on fetal growth, with increased fetal abdominal growth and reduced fetal head growth. Maternal chronic stress increases fetal cortisol, glucose and c-peptide secretion. Abstract: Introduction: During pregnancy, maternal stressors cause changes in both maternal and fetal HPA axes. We therefore investigated the impact of maternal non chronic and chronic stress on fetal glucose metabolism and growth, and serum levels of cortisol in the fetus. Materials and methods: Normal weight pregnant women (n = 192; mean ± SD 27.9 ± 4.2 years old, and; 26.9 ± 2.4 kg/m²) were assessed during the 2nd and 3rd trimester with anthropometry, fetal ultrasound, blood samples for serum CRH, cortisol and IL6, and STAI trait and state stress questionnaires. We measured serum cortisol, insulin and c-peptide, and plasma glucose from cord blood. Neonates underwent anthropometry at the 3rd post-delivery day. Results: In both 2nd and 3rd trimesters, women with STAI trait scores ≥40 had significantly greater levels of fasting serum CRH and cortisol than those with STAI trait scores<40. 2nd trimester: STAI trait scores correlated positively with cord blood glucose and c-peptide. Maternal serum CRH correlated negatively with U/S fetal biparietal head diameter, while serum cortisol correlated positively with abdominal circumference. Maternal serum IL6, CRH and cortisol all correlated positively with birth waist circumference. 3rd trimester: Women with STAI state scores ≥40 had fetuses with larger U/S abdominal and smaller head circumferences compared to those of women with STAI scores <40. Women with STAI trait scores ≥40 had greater levels of cord blood cortisol, glucose, and c-peptide compared to women with STAI scores <40. STAI state scores ≥40 correlated positively with maternal CRH and U/S fetal abdominal circumference, and negatively with fetal head circumference and biparietal diameter. STAI trait scores correlated positively with cord blood c-peptide, glucose, insulin and cortisol. Maternal serum levels of CRH correlated positively with U/S fetal abdominal circumference and cord blood cortisol, and negatively with fetal head circumference and biparietal head diameter. Maternal serum levels of both CRH and cortisol correlated positively with cord blood c-peptide, glucose, and insulin. STAI trait was the best positive predictor of cord blood cortisol, glucose and c-peptide, whilst STAI state was the best positive and negative predictor, respectively of fetal abdominal circumference and fetal head circumference or biparietal diameter. Conclusions: Increased maternal chronic stress (reflected by the STAI trait score) associates with increased fetal cortisol, glucose, c-peptide secretion and thus, insulin resistance. Maternal non chronic stress (STAI state) in the 3rd trimester associates with changes in fetal growth pattern, including increased and decreased measurements of fetal abdominal and head growth respectively.